2015
DOI: 10.1039/c4cy01168f
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the catalytic oxidation of benzyl alcohol using supported phosphine-capped gold nanoparticles

Abstract: Two phosphine-stabilised gold clusters, Au 101 (PPh 3 ) 21 Cl 5 and Au 9 (PPh 3 ) 8 (NO 3 ) 3 , were deposited and activated on anatase TiO 2 and fumed SiO 2 . These catalysts showed almost a complete oxidation of benzyl alcohol (>90 %) within 3 hours at 80 °C and 3 bar O 2 in methanol with a high substrate-to-metal molar ratio of 5800 and turn-over frequency of 0.65 s -1 . Factors influencing catalytic activity were investigated, 10 including metal-support interaction, effects of heat treatments, chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 93 publications
4
60
1
1
Order By: Relevance
“…The fundamental study reported herein is therefore intended to act as a foundation for further studies on the applications of these materials. [25][26][27] In the proceeding sections we present X-ray photoelectron spectroscopy (XPS) measurements of the gold core, the triphenylphosphine periphery, and the titanium dioxide support respectively. Following this, we present results of the UV-vis DRS spectroscopy investigations of these (and related) materials, which support the conclusions obtained from XPS data.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental study reported herein is therefore intended to act as a foundation for further studies on the applications of these materials. [25][26][27] In the proceeding sections we present X-ray photoelectron spectroscopy (XPS) measurements of the gold core, the triphenylphosphine periphery, and the titanium dioxide support respectively. Following this, we present results of the UV-vis DRS spectroscopy investigations of these (and related) materials, which support the conclusions obtained from XPS data.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies found that small clusters rather than nanoparticles are the catalytically active species [41], but such clusters may require high surface areas of the support material [42]. In contrast, slightly larger particles in the nanometer range (≈7 nm) are most active in alcohol oxidation [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In order to exploit the applicability of the present catalytic system and to generalize the scope of the oxidation process, the oxidation reaction has extended to various types of alcohol such as primary aromatic, allylic, heteroaromatic, and aliphatic alcohols. Generally, all primary aromatic alcohols could be oxidized rapidly to the corresponding aldehydes with complete conversions within very short reaction times (Table 6, entries [10][11][12][13][14][15][16][17][18][19][20][21][22]. Moreover, more than 99% selectivity to corresponding aldehydes has been achieved in most of oxidation reactions and no other products were detected in the reaction mixture because no overoxidation to carboxylic acids occurred.…”
Section: Oxidation Of Different Types Of Alcohols Over 1%mentioning
confidence: 96%
“…In contrast, using clean and low cost oxidizing agents, such as aqueous hydrogen peroxide and particularly molecular oxygen to produce water, is the only side product and has gained growing interest from the sustainable and green chemistry point of views [14,15]. In this context, noble metals such as gold [16][17][18][19][20], palladium [21], platinum [22][23][24], ruthenium [25,26], and rhodium [27,28] have been used as a heterogeneous catalyst for the alcohol oxidation with high catalytic activities and selectivities. Beside their high costs, these precious metals also have serious toxicity issues and difficulty in preparation and rarity of these noble metals makes these catalysts 2 Journal of Chemistry impractical for industrial applications [29,30].…”
Section: Introductionmentioning
confidence: 99%